2013
DOI: 10.1021/jp409022m
|View full text |Cite
|
Sign up to set email alerts
|

Conformers of Cysteine and Cysteine Sulfenic Acid and Mechanisms of the Reaction of Cysteine Sulfenic Acid with 5,5-Dimethyl-1,3-cyclohexanedione (Dimedone)

Abstract: Equilibrium and molecular structures, relative energies of conformers of gaseous cysteine (Cys, C, Cys-SH) and gaseous cysteine sulfenic acid (Cys-SOH), and the mechanisms of the reaction of Cys-SOH with 3-hydroxy-5,5-dimethyl-2-cyclohexen-1-one, the enol tautomer of 5,5-dimethyl-1,3-cyclohexadione (dimedone), have been studied using BD(T), CCSD(T), and QCISD(T) with the cc-pVTZ basis set and using MP2 and the density functionals B3LYP, B3PW91, PBE1PBE, PBEh1PBE, M062X, CAM-B3LYP, and WB97XD with the 6-311+G(d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 99 publications
2
18
0
Order By: Relevance
“…1) to form sulfides (thioethers). [1][2][3] In this manuscript, the investigation of an alternative reaction that leads to sulfenic ester formation through O-sulfenylation is presented and supported (Fig. 1).…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…1) to form sulfides (thioethers). [1][2][3] In this manuscript, the investigation of an alternative reaction that leads to sulfenic ester formation through O-sulfenylation is presented and supported (Fig. 1).…”
mentioning
confidence: 80%
“…1) is reasonable. 2 It is known that electrophilic sulfenyl sulfur reacts with nucleophiles such as alkenes, enamines, and enols. Owing to the vital importance and significance of the chemoselectivity of 1,3-cyclohexanedione (1) and 5,5-dimethyl-1,3-cyclohexanedione (2) in detecting protein sulfenic acids, it is important to understand the fundamental mechanisms and products of the sulfenylation reactions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to steric and electrostatic interactions mentioned above, these include intrinsic protein motions and dynamic structural changes induced by oxidation. Computational studies, for example, found that the lowest energy conformer of cysteine -SOH harbors four hydrogen-bonding interactions, which were proposed to impact both -SOH formation and stability [16]. Similar to small molecule -SOH, protein -SOH species can exist as stable products of thiol oxidation or can react with other moieties to produce disulfides (e.g., reaction with free or protein thiols, -SSR), thiosulfinate (reaction with other -SOH, -S(=O)SCys), sulfinic or sulfonic states (hyperoxidation, -SO 2/3 H), and sulfenyl amides (-SN).…”
Section: Synthesis Stability Reactivity and Characterization Of mentioning
confidence: 99%